Morphometric and meristic variation in the Atlantic chub mackerel Scomber colias Gmelin, 1789 from the Moroccan coast - Bouzzammit, N.; El Ouizgani, H. (Indian Journal of Fisheries, 2019)
Morphometric and meristic characters were used to study the variability between Scomber colias Gmelin, 1789 sampled from five locations in the Moroccan Atlantic coast. Â Eighteen morphometric measurements were taken using the image processing program, Image j along with seven meristic characters. Univariate analysis of variance (ANOVA) performed by Tukey HSDÂ post-hoc test showed significant differences for 14 standard morphometric measurements. In principal component analysis (PCA),PC1 was resolved as general size and PC2 was resolved as shape differences. Discriminant analysis indicated the existence of four morphometric groups of S. colias with minor overlapping, which suggested that there is a self-recruiting population. The proportion of correctly classified Sidi Ifni (SDF) sample to their original group was 96% and showed clear separation from other groups. We concluded that Sidi Ifni samples are morphologically distinct from S. colias of the other four localities which could be attributed to genetic bias or environmental factors. Keywords: Agadir, Meristic, Morocco, Morphometric, Scomber colias